Some Ambarzumyan Type Theorems for Bessel Operator on a Finite Interval - Yilmaz, Emrah; Koyunbakan, Hikmet (Springer India, 2019)
In this study, we deal with an inverse problem for Bessel operator on a finite interval. We present some results of the associated with Ambarzumyan's theorem by using spectrum and nodal points (zeros of eigenfunction).
Keywords: Spectrum; Ambarzumyan theorem; Bessel operator; Nodal points; 34A55; 34L05; 34L20